2002
DOI: 10.1093/ps/81.9.1347
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a chicken breed by inter se mating of germline chimeric birds

Abstract: Blastoderm cells from chicken embryos of a donor breed (Green-legged Partridgelike; GP) were transferred to embryos of a recipient breed (White Leghorn; WL) to form chimeric progeny that, after inter se mating, permitted successful reconstitution of the donor breed. Among 23 chimeric chicks hatched from WL embryos injected with GP cells, 20 (87%) were raised until maturity, and progeny were tested by mating with GP birds to determine the ability of blastodermal cells to form germline chimeras. Six of the teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Chimeric chickens were bred in general by two different procedures: (i) blastodermal cells (BCs) containing primordial germ cells (PGCs) or their precursors, isolated from stage X (Eyal‐Giladi and Kochav, 1976) chicken embryo, injected into subgerminal cavity of recipient embryo (Marzullo, 1970); (ii) primordial germ cells isolated from germinal crescent, blood or gonads of donor embryos and transferred directly into bloodstream of the recipient embryos (Yasuda et al., 1992). In our laboratory, the production of chicken somatic and germline chimeras has been conducted (Bednarczyk et al., 2002, 2003) by the transfer of donor BCs into windowed eggs, according to the method proposed by Petitte et al. (1990), with some modifications (Bednarczyk et al., 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimeric chickens were bred in general by two different procedures: (i) blastodermal cells (BCs) containing primordial germ cells (PGCs) or their precursors, isolated from stage X (Eyal‐Giladi and Kochav, 1976) chicken embryo, injected into subgerminal cavity of recipient embryo (Marzullo, 1970); (ii) primordial germ cells isolated from germinal crescent, blood or gonads of donor embryos and transferred directly into bloodstream of the recipient embryos (Yasuda et al., 1992). In our laboratory, the production of chicken somatic and germline chimeras has been conducted (Bednarczyk et al., 2002, 2003) by the transfer of donor BCs into windowed eggs, according to the method proposed by Petitte et al. (1990), with some modifications (Bednarczyk et al., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Blastodermal cells are pluripotent and when transferred from donor to recipient embryos can contribute to different embryonic cell types including the germline. Chimerism is demonstrated routinely using feather (Petitte et al., 1990) and shell colouring (Czekalski, 2004), analysis of sex chromosomes from a sex‐mismatched donor (Simkiss et al., 1996; Kagami et al., 2002) or analysis of polymorphic DNA sequences (Bednarczyk et al., 2002; Naito et al., 2004) by using a marker. However, only few studies have attempted to study the effect of donor cells on physiology, development and production of post‐hatch chickens.…”
Section: Introductionmentioning
confidence: 99%
“…A series of intraspecies chimeras and donor cell-derived offspring have been reported in previous studies using blastodermal cell transfer (Carsience et al, 1993;Kagami et al, 1997;Kino et al, 1997;Speksnijder and Ivarie, 2000;Naito et al, 2001). Based on intraspecies technology, intergenus and interorder germline chimeras have been obtained between Japanese quail and White Leghorn (WL) (Naito et al, 1991), Green-legged Partridgelike and WL (Bednarczyk et al, 2002), Maya duck and WL (Li et al, 2002), and Japanese quail and Peking duck as shown in Figure 1A, B (Gao et al, 2011). Intergenus and interorder germline chimeras and progenies were successfully produced by Green-legged Partridgelike-WL (Bednarczyk et al, 2002) and Maya duck-WL chimeras as shown in Figure 1C, D (Li et al, 2002) using blastodermal cell injection, but the efficiency of progeny production was low.…”
Section: Chimera Production Using Blastodermal Cellsmentioning
confidence: 98%
“…Based on intraspecies technology, intergenus and interorder germline chimeras have been obtained between Japanese quail and White Leghorn (WL) (Naito et al, 1991), Green-legged Partridgelike and WL (Bednarczyk et al, 2002), Maya duck and WL (Li et al, 2002), and Japanese quail and Peking duck as shown in Figure 1A, B (Gao et al, 2011). Intergenus and interorder germline chimeras and progenies were successfully produced by Green-legged Partridgelike-WL (Bednarczyk et al, 2002) and Maya duck-WL chimeras as shown in Figure 1C, D (Li et al, 2002) using blastodermal cell injection, but the efficiency of progeny production was low. In our latest experiments, we produced chimeras in different classes (Peking duck and Chinese soft-shelled turtle).…”
Section: Chimera Production Using Blastodermal Cellsmentioning
confidence: 99%
“…Germline chimeras are one of the best tools for studying bird embryo development (Tagami & Kagami, ), as well as to produce the transgenic birds (Ono et al., ; Tajima, Naito, Yasuda, & Kuwana, ) or to reconstitute endangered species (Bednarczyk et al., ). Many years of bird embryo research provided different methods of localizing primordial germ cells (PGCs), which are used to obtain germline chimeras—beginning with periodic acid‐Schiff (PAS) staining technique (Ginsburg & Eyal‐Giladi, ; Muniesa & Dominguez, ), to immunostaining (Karagenç, Cinnamon, Ginsburg, & Petitte, ).…”
Section: Introductionmentioning
confidence: 99%